The System of Integrated Performance Evaluation of the Effectiveness of Service Production in the Gas Transportation Industry - Бакай, М. Л. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
Reviewed the methodological principles and theoretical approaches to assessing the level of efficiency and service capacity of gas transportation business sector. Determined system of indicators to measure individual components of potential service enterprises which are allocated among the following groups: human resources, financial, industrial, and institutional capacity.The necessity of building integrated parameter estimation efficiency and the use of the service capacity of enterprises through the use of functions Harrynhtona. Proposed a unique method of estimating the potential efficiency of service that will comprehensively evaluate the level of use. Based on theoretical generalizations and methodological studies towards evaluating the potential of the basic economic decisions can be taken on the results of calculations and assessing the effectiveness of the use of the service potential of the proposed method.